The effectiveness of spelling bee game through students’ vocabulary mastery - Nyoman Karina Wedhanti; Ni Made Ratminingsih; Kadek Samiyanti (UPT Bahasa Universitas Tanjungpura, 2021)
This study aimed at investigating whether or not there was a significant difference in vocabulary mastery between the students who were taught by using spelling bee game and those who were taught by using memorization through flash card. This research was quasi-experimental in nature. This study was conducted in pre-test and post-test design. The population was students of the fourth grade in elementary school in SD Negeri 3 Banjar Jawa. Random Sampling was assigned to determine the samples of the study. There were 30 students in Class A as the experimental group which was taught by using spelling bee game and 30 students in Class B as the control group which was taught by using memorization through flash card. The obtained data were analyzed through descriptive analysis and inferential analysis. The effect size was calculated by using Cohen’s d testing. Based on the findings, the result proved that there was a significant difference in students’ vocabulary mastery. The students who were taught using Spelling bee game also showed positive attitude during the learning process. There were three reasons why spelling bee game was better to be implemented, namely it helps the students to remember words better, it is enjoyable, and it makes students more active.